Gas chromatography vacuum ultraviolet spectroscopy: A review. Issue 1 (10th December 2019) - Lelevic, Aleksandra; Souchon, Vincent; Moreaud, Maxime; Lorentz, Chantal; Geantet, Christophe
Abstract: Accelerated technological progress and increased complexity of interrogated matrices imposes a demand for fast, powerful, and resolutive analysis techniques. Gas chromatography has been for a long time a 'go‐to' technique for the analysis of mixtures of volatile and semi‐volatile compounds. Coupling of the several dimensions of gas chromatography separation has allowed to access a realm of improved separations in the terms of increased separation power and detection sensitivity. Especially comprehensive separations offer an insight into detailed sample composition for complex samples. Combining these advanced separation techniques with an informative detection system such as vacuum ultraviolet spectroscopy is therefore of great interest. Almost all molecules absorb the vacuum ultraviolet radiation and have distinct spectral features with compound classes exhibiting spectral signature similarities. Spectral information can be 'filtered' to extract the response in the most informative spectral ranges. Developed algorithms allow spectral mixture estimation of coeluting species. Vacuum ultraviolet detector follows Beer–Lambert law, with the possibility of calibrationless quantitation. The purpose of this article is to provide an overview of the features and specificities of gas chromatography–vacuum ultraviolet spectroscopy coupling which has gained interest since the recent introduction of a commercial vacuum ultraviolet detector. Potentials and limitations, relevant theoretical considerations, recent advances and applications are explored.